Analisis Jumlah Ismiyah Dan Metode Pembelajarannya Dalam Al-Quran Surah Al-Qolam: Analisis Jumlah Ismiyah - Sastrawan, Doni (An Naba, 2019)
The background of this research is the importance of understanding the nahwu science which is very influential on the meaning of sentences and the number of inaccurate understandings about the number of Ismiyah. This Thesis Discusses the Number of Ismiyah and its learning in the Al-Qur'an Surat Al-Qolam. The formulation of the problem in research is how to use the number of Ismiyah in Al-Qolam and its learning. In addition, this study aims to find out and describe the analysis of the number of Ismiyah through the nahwu science approach and to know the number of Ismiyah found in the Al-Qolam letter. This research is a library research (library research) that is research that takes research materials from several references or books that fit the research theme by taking data from Al-Qur'an surah Al-Qolam using descriptive analysis. The data collection by observation of primary and secondary data sources qualitatively. The structure of the Ismiyah Amount in Surat Al-Qolam is very diverse, which includes Mubtada 'Isim Mabni, Mubtada' Isim Mu'rab, as well as Khabar mufrad, Khabar Quantity, Khabar Syibhul Quantity. The results of research from the Al-Qolam letter there are 26 Ismiyah. Through this research it is hoped that it can provide benefits and can be used as literature in the study of literature review.